2015
DOI: 10.1007/s10637-015-0255-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of the heat shock protein 90 (Hsp90) inhibitor onalespib (AT13387) administered on a daily for 2 consecutive days per week dosing schedule in patients with advanced solid tumors

Abstract: Inhibition of heat shock 90 (Hsp90) molecular chaperones allows targeting of multiple proteins involved in tumorigenesis. We investigated the safety, recommended phase 2 dose (RP2D), and pharmacokinetic and pharmacodynamic profile of onalespib (AT13387), a potent synthetic Hsp90 inhibitor, administered on days 1, 2, 8, 9, 15, and 16 of 28 day cycles (QDx2/week) in a phase I trial. This study followed an accelerated titration design with a starting dose of 20 mg/m(2)/dose and a standard 3 + 3 dose escalation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 14 publications
4
32
0
Order By: Relevance
“…The list of HSP90 client proteins is long and includes proteins involved in proliferation, DNA repair and angiogenesis, such as EGFR and VEGFR [17,18]. In addition, HSP90 inhibition may also lead to upregulation of a related heat shock protein, HSP70 (HSP72, HSPA1A) [19][20][21], a protein thought to play a protective role in renal damage [22][23][24].…”
Section: This Article Is Part Of the Topical Collection On Translatiomentioning
confidence: 99%
“…The list of HSP90 client proteins is long and includes proteins involved in proliferation, DNA repair and angiogenesis, such as EGFR and VEGFR [17,18]. In addition, HSP90 inhibition may also lead to upregulation of a related heat shock protein, HSP70 (HSP72, HSPA1A) [19][20][21], a protein thought to play a protective role in renal damage [22][23][24].…”
Section: This Article Is Part Of the Topical Collection On Translatiomentioning
confidence: 99%
“…This suggests that targeting HSP90 could potentially overcome these resistance mechanisms and improve sensitivity to therapies (15, 16). Currently, several HSP90 inhibitors are being evaluated in trials against solid tumors and are in different stages of clinical development (1719). They bind to the N-terminal ATPase-pocket, affecting the chaperone activity and leading to the depletion of HSP90 substrates by subsequent proteosomal degradation (1113).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in several solid tumor models have shown sensitization to currently used chemotherapeutic agents when combined with new generation HSP90 inhibitors (20, 21). Onalespib, a potent second-generation HSP90 inhibitor differs from other HSP90 inhibitors in its longer duration of target inhibition (22) and its favorable toxicity profile in phase I studies in patients with refractory solid tumors (17). However, there is no significant preclinical data regarding the effects of onalespib against glioblastoma; in addition, the potential for chemosensitization of onalespib in combination with alkylating agents such as temozolomide (TMZ) has not been previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in HSP90 can contribute to the upregulation of HSF-1, as inhibition of HSP90 triggers the heat shock response (Zou et al, 1998). Upon upregulation of HSF-1, there is an elongated occupation of HSF-1 on the HSP70 gene resulting in increased levels of HSP70 (Do et al, 2015;Shapiro et al, 2015). Downregulation of HSP90 and upregulation of sHSP-HSP70-BAG3 may thus be functionally linked in Alzheimer neurons.…”
Section: Stress Responsementioning
confidence: 99%